Karyotype differentiation in three species of Tripogandra Raf. (Commelinaceae) with different ploidy levels - André Marques; Fernando Roa; Marcelo Guerra (Genetics and Molecular Biology, 2010)
Most species of the genus Tripogandra (Commelinaceae) are taxonomically poorly circumscribed, in spite of having a relatively stable basic number x = 8. Aiming to estimate the cytological variation among Tripogandra species carrying this base number, several structural karyotypic characters were investigated in the diploid T. glandulosa, the hexaploid T. serrulata, and the octoploid T. diuretica. A careful evaluation of chromosome size and morphology did not reveal clear chromosome homeologies among karyotypes. The mean chromosome size was strongly reduced in the octoploid species, but not in the hexaploid species. They also differed largely in the CMA+ banding pattern and in the number of 5S and 45S rDNA sites per monoploid chromosome complement. All three species showed proximal DAPI+ heterochromatin, although in T. serrulata this kind of heterochromatin was only visible after FISH. Further, the meiosis in T. serrulata was highly irregular, suggesting that this species has a hybrid origin. The data indicate that, in spite of the conservation of the base number, these species are karyologically quite different from each other.